Marine litter in bottom trawls off the Portuguese coast. Issue 1 (15th October 2015) - Neves, Diogo; Sobral, Paula; Pereira, Tânia
Highlights: Marine litter data from 135 bottom trawls at depth range of 90–349 m off Portugal. 2034 items recorded, 76% were plastic and 38.6% originated from fishing activities. Highest density (178.9 ± 64.0 items km −2 ) was found near the Tagus river mouth. Most abundant items were pieces of trawl nets, packaging, cords and plastic bags. Fishermen awareness on good environmental practices toward marine litter is needed. Abstract: Benthic marine litter along the Portuguese coast, was recorded in 14 trips on stern trawlers covering a distance of 2117 km and an area of 56.2 km 2, average depth range 90–349 m. 2034 items of marine litter were registered, 76% were plastics and 38.6% were originated from fishing related activities. Plastic was present in all the trawls and had the highest average density of all litter categories, 50 items km −2 . The highest density of marine litter (178.9 ± 64.0 items km −2 ) was found in the proximity of the Tagus river mouth, probably related to the high population density in the Lisbon metropolitan area. This study highlights the need to raise fishermen awareness for the adoption of good environmental practices that will contribute to the reduction of marine litter.